2016
DOI: 10.2147/ceor.s112252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating increased resource use in fibromyalgia using electronic health records

Abstract: ObjectiveThe management of fibromyalgia (FM), a chronic musculoskeletal disease, remains challenging, and patients with FM are often characterized by high health care resource utilization. This study sought to explore potential drivers of all-cause health care resource utilization and other factors associated with high resource use, using a large electronic health records (EHR) database to explore data from patients diagnosed with FM.MethodsThis was a retrospective analysis of de-identified EHR data from the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 28 publications
3
19
3
Order By: Relevance
“…The majority of studies were from USA ( n = 28) , followed by UK ( n = 4 studies) , Spain ( n = 3 studies) and Canada ( n = 3 studies) , with single studies from Norway , Denmark , Australia and India . There were no studies that compared data from multiple countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies were from USA ( n = 28) , followed by UK ( n = 4 studies) , Spain ( n = 3 studies) and Canada ( n = 3 studies) , with single studies from Norway , Denmark , Australia and India . There were no studies that compared data from multiple countries.…”
Section: Resultsmentioning
confidence: 99%
“…There were 5 059 098 patients with chronic noncancer pain across the 42 studies. Twenty‐seven studies (64%) included specific subgroups of chronic noncancer pain such as chronic low back pain , osteoarthritis , rheumatoid arthritis and fibromyalgia . The mean age of participants was 58.6 years (SD 13.1, n = 29 studies).…”
Section: Resultsmentioning
confidence: 99%
“…The few studies on opioids for the treatment of FM have suggested that while responders to the weak opioid tramadol may have a reduction in pain but not in health‐related quality of life, opioids may have contributed to increased resource use and costs, or less favorable outcomes . The current study expands on the evaluated effectiveness of opioids for FM by showing that although opioids may provide benefits in pain and pain interference outcomes, treatment with pregabalin, which is approved for the treatment of FM, appeared to provide more favorable outcomes relative to opioids.…”
Section: Discussionmentioning
confidence: 71%
“…In the United States, the Food and Drug Administration (FDA) has approved 3 drugs for the treatment of FM: 2 antidepressants (duloxetine and milnacipran) and an anticonvulsant (pregabalin). However, treatment of FM remains challenging, and studies have shown low or ineffective use of approved or recommended therapies, with opioids consistently reported as the most frequently prescribed pharmacologic agent despite little evidence for their efficacy . Indeed, studies have suggested that opioid use may be associated with higher healthcare resource utilization and costs among patients with FM .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation